Coral Reef Fishes Biodiversity In Pahawang Island,Pesawaran District Lampung - Yuliana, Darma; Rahmasari, Ayu; Yulianto, Herman; Damai, Abdullah Aman (AQUASAINS, 2020)
The components of coral reef ecosystem can be described by the unique regulation in community level. Coral reef fishes use coral reef as their habitat and they highly depend on coral reef health. Otherwise, the condition of coral reef health can be predicted by the biodiversity of coral reef fishes. The research aim was describe communities differences between two explored area in marine tourism spots in Pahawang Island. This research was conducted on November 2019 at two stations on the coral reefs ecosystem of Pahawang Island represented the two quitely different area, the marine tourism and the visitor areas. The coral reef fishes were observed by using visual census method with a Line Transect length of 30 meters and a visibility of 2.5 meters left and right of the transect. Coral reef fish community structure was measured by diversity, similarity, and dominancy indexes. A total of 1.940 coral reef fish species from 13 families were recorded. Pomacentridae is the most speciose family (1.091 species), followed by Siganidae (308 species) and Labridae (166 species). Biodiversity of coral reef fishes at Pahawang Island showed results diversity index (H') in both observation stations classified as medium with a low dominance index value (C) and similarity index (E) at both stations classified as high, presumably as a result of tourism activities. The diversity index at station 2 has a greater value than station 1 as a tourist area with diving and snorkeling tourism activities, at station 2 there are more types or genus of reef fish, compared to station 1.